Inhibition of Sterol Biosynthesis by Bacitracin - Stone, K. John (1972)
Bacitracin is an inhibitor of the biosynthesis of squalene and sterols from mevalonic acid, C(5)-isopentenyl pyrophosphate, or C(15)-farnesyl pyrophosphate catalyzed by preparations from rat liver. The antibiotic is active at extremely low ratios of antibiotic to substrate. The mechanism of inhibition appears to be the formation of a complex between bacitracin, divalent cation, and C(15)-farnesyl pyrophosphate and other isoprenyl pyrophosphates. It is similar to the formation of the complex with C(55)-isopropenyl pyrophosphate in microbial systems. The toxicity of bacitracin for animal cells could be due in part to the formation of these complexes.